Efektivitas Pistia stratiotes dan Salvinia molesta sebagai Agen Fitoremediasi Limbah Sungai Ciliwung - Aulya, Nailul Rahmi; Ristanto, Rizhal Hendi; Nurazizah, Meiza; Febryaningrum, Sukma; Muthiah, Anis; Fauziyah, Fina (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Rapid development and increasing population growth affect river water quality, including the Ciliwung River. The decline in the water quality of the Ciliwung River is caused by organic waste originating from households, industry, livestock, and agriculture, so efforts are being made to manage the water using phytoremediation. Pistia stratiotes and Salvinia molesta are aquatic plants that can absorb heavy metals in polluted water. This research aims to determine the effectiveness of plants Pistia stratiotes and Salvinia molesta in reducing the Ciliwung River's wastewater level. This type of research is laboratory-scale experimental with RAL in 3 treatments (A, B, and C) and 6 replications. Data were analyzed using the ANOVA test with the DMRT further test. The results of the research showed that the treatment of two types of plants had a significant effect on reducing the level of water turbidity with the greatest reduction rate being found in plants Salvinia molesta. The fastest change in color and reduction in the number of leaves occurs in plants Pistia stratiotes, and the levels of AAS contaminants before and after treatment cannot be detected because the detection limit of the smallest limit test parameter possessed by a tool/instrument for measuring a certain number of analytes is different.